2013
DOI: 10.1074/jbc.m113.474650
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Autophagy Limits Cardiac Injury in Mouse Models of Type 1 Diabetes

Abstract: Background: Autophagy activity is reduced in type 1 diabetic heart, but the functional role remains unclear. Results: Further reduction in autophagy protects against diabetic heart injury, whereas restoration of autophagy exacerbates cardiac damage. Conclusion:The diminished autophagy limits cardiac dysfunction in type 1 diabetes. Significance: Understanding the functional role of autophagy will facilitate drug design to fight diabetic heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
198
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(224 citation statements)
references
References 57 publications
13
198
0
2
Order By: Relevance
“…The present study demonstrated that the diabetic myocardium is associated with reduced expression of PINK1 and Parkin, suggesting that mitochondrial quality control via the PINK1/Parkin pathway is influenced. These results are consistent with a previous study, which indicated that mitophagy was reduced in diabetic hearts 58. This group also reported mitochondrial dysfunction and accumulation of dysfunctional mitochondria in the diabetic myocardium.…”
Section: Discussionsupporting
confidence: 93%
“…The present study demonstrated that the diabetic myocardium is associated with reduced expression of PINK1 and Parkin, suggesting that mitochondrial quality control via the PINK1/Parkin pathway is influenced. These results are consistent with a previous study, which indicated that mitophagy was reduced in diabetic hearts 58. This group also reported mitochondrial dysfunction and accumulation of dysfunctional mitochondria in the diabetic myocardium.…”
Section: Discussionsupporting
confidence: 93%
“…[33][34][35][36] In addition, elimination of damaged mitochondria by mitophagy was reported to be relatively deficient or decreased in the cardiac musculature of patients with diabetes. 37 Similarly, two mitophagy regulators, Pink1 and Parkin (the genes that are relevant in the pathogenesis of Parkinson disease), were found to be downregulated in cardiac and skeletal muscles in diabetic states. 37,38 In this study, we observed that most of the mitochondria within the injured tubules in STZinduced diabetic mice were fragmented and had a randomly disorganized cellular distribution (Figures 6F and 7B).…”
Section: Discussionmentioning
confidence: 99%
“…37 Similarly, two mitophagy regulators, Pink1 and Parkin (the genes that are relevant in the pathogenesis of Parkinson disease), were found to be downregulated in cardiac and skeletal muscles in diabetic states. 37,38 In this study, we observed that most of the mitochondria within the injured tubules in STZinduced diabetic mice were fragmented and had a randomly disorganized cellular distribution (Figures 6F and 7B). At the same time, the cellular autophagic vacuoles and mitophagy were reduced in tubules, indicating less efficient removal of damaged mitochondria and a compromised surveillance mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that cardiac complications are major causes of mortality in patients with diabetes mellitus, therapeutic conceptions to prevent diabetic myocardiopathy remain inaccessible due to only partial understanding of the underlying mechanisms (1,2). Diabetic cardiomyopathy was first recognized by Rubler et al in patients with diabetes (3).…”
Section: Introductionmentioning
confidence: 99%